2013
DOI: 10.1111/jels.12019
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing Confidence in the Judicial System: Introducing Lay Participation in Taiwan

Abstract: Using Taiwan's 2012 proposal as an illustration, this article discusses a new form of lay participation-the advisory jury-where a group of lay jurors make a collective decision without the professional judges' interference but such decision has no binding effect. This article analyzes how identifying promotion of the public's confidence in the judicial system rather than democratizing judicial decision making by legal elites as the reform purpose leads to the emergence of this form of lay participation. Throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This change is consistent with resurgence over the last two decades of lay participation in the adjudication process. Russia (1993) and Spain (1995) introduced jury systems most recently in Europe (Thaman, 2000), but Huang and Lin (2013) note that such changes have also occurred in Central Asia (e.g., Azerbaijan, Georgia, Kazakhstan, Russia, Tajikistan, Ukraine, and Uzbekistan) and in East Asia, including Japan, South Korea, and Taiwan. This embracing of lay participation (whether as jurors or lay judges) has been described as similar to that occurring in 19th-century Europe under the influence of the 1789 French Revolution and is being used as a means of democratizing the countries’ legal system (Fukurai, Chan, & Miyazawa, 2010a, 2010b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This change is consistent with resurgence over the last two decades of lay participation in the adjudication process. Russia (1993) and Spain (1995) introduced jury systems most recently in Europe (Thaman, 2000), but Huang and Lin (2013) note that such changes have also occurred in Central Asia (e.g., Azerbaijan, Georgia, Kazakhstan, Russia, Tajikistan, Ukraine, and Uzbekistan) and in East Asia, including Japan, South Korea, and Taiwan. This embracing of lay participation (whether as jurors or lay judges) has been described as similar to that occurring in 19th-century Europe under the influence of the 1789 French Revolution and is being used as a means of democratizing the countries’ legal system (Fukurai, Chan, & Miyazawa, 2010a, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…When the defendant agrees to this procedural addition, randomly selected civilian participants hear testimony then deliberate on their own before consulting with professional judges regarding guilt and, as necessary, punishment (Kim, Park, Park, & Eom, 2013; J.-H. Lee, 2009, 2010). Similarly, Taiwan is considering a proposal wherein a group of five randomly chosen citizens would sit with and advise three professional judges in serious criminal trials (Huang & Lin, 2013, 2014). To the extent, Japan is able to set an Asian model for ordinary citizens to participate in deciding criminal cases, the saiban-in system could be a major event of the early 21st century.…”
Section: Discussionmentioning
confidence: 99%
“…A few leading cases rendered by the Supreme Court of Taiwan in the 1950s and 1960s declared that the following factors Judges in Taiwan are career judges who serve on the bench after passing a judiciary examination and receiving training for two years. As of December 2015, there is no jury system in Taiwan, though a pilot program on introducing a "lay observer system" is under way (Huang & Lin 2013).…”
Section: Taiwan's Pain and Suffering Damages Lawmentioning
confidence: 99%
“…In evaluating the desirability of using laypeople as adjudicators in criminal trials, one issue was whether Taiwanese citizens would appreciate the legal norm that the disutility of convicting an innocent person is much greater than the disutility of freeing a guilty one. The latest national survey in Taiwan showed that only about 40% of Taiwanese citizens thought that it is more serious and undesirable to convict an innocent person than to acquit a guilty one (Huang & Lin, 2013). This finding led to the concern that laypeople might be more tolerant of wrongful conviction in order to suppress wrongful acquittal than professional judges, and this tolerance might threaten to undermine the value underpinning the principle of presumption of innocence.…”
Section: Research Questionsmentioning
confidence: 99%
“…Under the proposed system, a group of five randomly chosen citizens would participate in criminal trials for specific types of serious offenses and form an advisory opinion by a simple majority. The lay observers’ collective opinion would not be binding upon a panel of three professional judges, who would ultimately decide a defendant’s guilt (Huang & Lin, 2013). Although the idea of introducing lay participation has wide support in Taiwan, the official proposal has been fiercely criticized by civic groups (Alliance for Promoting Lay Participation, 2012).…”
mentioning
confidence: 99%